Investigating the Two-Dimensional Distribution of Soil pH and Phosphorus in the Charosphere: A Short-Term Incubation Experiment - Xuejiao Chen; Feng Gu; Dongdong Zhang; Wei Lin; Jie Tang; Bin Zhang; Xuan Yu (Agronomy)
Biochar, which contains abundant nutrients like phosphorus (P), is considered a potential source of nutrients for plant use after its application in soil. However, the localized distribution of P in the vicinity of biochar (that is, the charosphere) is poorly understood. In this study, the biochars derived from pinewood (PWB), maize straw (MSB), and chicken manure (CMB) were granulated and investigated for their short-term charosphere effect, using an integrated imaging technique in situ. The results showed that biochars significantly elevated the soil pH and P concentration around their granules, leading to the development of a charosphere over several days. Both pH and P were distributed in a gradient in the charosphere: the values were highest where the biochars were located and declined with increasing distance from the biochar. A highly positive correlation (p < 0.01) was found between the pH, electric conductivity (EC), ash content of the biochar, and the scope of the pH gradient in the charosphere. Moreover, the scope of the P gradient was positively related to the pH and EC values of the biochar as well (p < 0.05). The charosphere effect was prominent around the CMB and MSB granules because of their high ash content, an especially soluble component. The P diffusion in the charosphere was inferred to be influenced by the soil pH as well as the endogenous P species in the biochars. These findings provide new insight into the localized effect of biochars in soil, which is conducive to understanding the nutrient availability to plants after biochar application.